Clientelism and Planning in the Informal Settlements of Developing Democracies. (November 2019) - Deuskar, Chandan
The informal provision of benefits to the poor in exchange for political support, known as clientelism, often provides access to land and services for the urban poor in informal settlements in developing democracies. This review of multidisciplinary literature finds that while clientelism provides the urban poor with some access to the state, its benefits are often inadequate and inequitable. This kind of informal provision also disincentivizes or interferes with the implementation of formal plans. The literature provides some examples of transitions away from clientelism, but lessons for planners in facilitating such transitions are elusive.